The Experiment of 3CM Learning Model on The Creative Thinking Ability of Junior High School Students in Salatiga Indonesia - Hafilda Suha Abidah; Erlina Prihatnani; Wahyudi Wahyudi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
Creative thinking skill needs to be trained, even though the learning is conducted online these days. One of the attempts in developing students’ creative thinking skill is through the implementation of 3CM (Cool-Critical-Creative-Meaningful) learning model. This study aimed at analyzing the students’ creative thinking skill through the implementation of the model with two different creative products (problem construction and non-problem construction) in flat-surfaced three-dimensional object. The population of this research was the whole Junior High School students in Salatiga City with the 80 samples of students from SMP Negeri 1 Salatiga and SMP Negeri 6 Salatiga. This study applied quasi experiment research with pretest-posttest control group design. The data were collected through written test and the result of observation on the students. The data analysis used involves initial balance test and hypothesis test using parametric test called Independent Sample T-Test with the significance rate of α=5%. Before being administered with different treatments, the two samples class were in a balanced condition. The findings presented that the implementation of 3CM (Cool-Critical-Creative-Meaningful) with creative activity of project and problem posing (constructing problem and solving constructed problem) for the material of flat-surfaced three-dimensional object proved to be significantly affect, equally, the creative thinking skill.